2014
DOI: 10.1177/0956797614538065
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Homo economicus

Abstract: Homo economicus, a model for humans in neoclassical economics, is a rational maximizer of self-interest. However, many social scientists regard such a person as a mere imaginary creature. We found that 31 of 446 residents of relatively wealthy Tokyo suburbs met the behavioral definition of Homo economicus. In several rounds of economic games, participants whose behavior was consistent with this model always apportioned the money endowed by the experimenter to themselves, leaving no share for their partners. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 23 publications
2
71
1
1
Order By: Relevance
“…Our perspective suggests that investigations of income and generosity will yield different results depending on the geographical areas where they are conducted. Accordingly, our research helps explain why studies conducted in one of the most unequal US states, California (6), found negative associations between income and generosity (e.g., participants with higher income gave fewer resources and were less helpful to others) (3), whereas studies conducted in less unequal areas (the Netherlands, Germany, and Japan) (13)(14)(15) found no such associations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our perspective suggests that investigations of income and generosity will yield different results depending on the geographical areas where they are conducted. Accordingly, our research helps explain why studies conducted in one of the most unequal US states, California (6), found negative associations between income and generosity (e.g., participants with higher income gave fewer resources and were less helpful to others) (3), whereas studies conducted in less unequal areas (the Netherlands, Germany, and Japan) (13)(14)(15) found no such associations.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, recent investigations conducted in the Netherlands and Germany, where there is considerably less inequality (6), found no association and a positive association, respectively, between income and how much participants in a "trust game" reciprocated the cooperative behavior of their partner (13,14). Furthermore, a study conducted in Japan, where inequality is also relatively low (6), found no association between a composite of income and related status indicators and giving behavior in dictator games (15). Although these findings suggest that a negative relation between income and generosity might emerge only under conditions of high inequality, whether the extent of inequality modifies the incomegenerosity link has never been systematically tested.…”
mentioning
confidence: 97%
“…In line with this prediction, little consistent association has been found between an individual's cognitive style and their overall willingness to cooperate in one-shot games (4,43,44). Furthermore, individual differences in reaction times, which are often interpreted as a proxy for intuitiveness (although see refs.…”
Section: Discussionmentioning
confidence: 99%
“…However, cultural differences in otherishness may depend on who the "other" is. People in collectivist cultures may be more otherish toward ingroup members but less otherish toward outgroup members (Yamagishi et al 2014). We also know little about cultural differences in the costs and benefits of selfishness and otherishness.…”
mentioning
confidence: 99%